Thrombosis of the torcular herophili in the fetus: a series of eight cases. (4th September 2014) - Corral, Edgardo; Stecher, Ximena; Malinger, Gustavo; Ochoa, Jose H.; de Catte, Luc; Sepulveda, Waldo
ABSTRACT Objective The objective of this study was to describe the prenatal sonographic and magnetic resonance imaging (MRI) findings, antenatal course, and pregnancy outcome in fetuses diagnosed as having thrombosis of the torcular herophili. Methods Retrospective review of cases collected from five fetal medicine referral centers. Results Eight cases that were prenatally diagnosed by ultrasound between 22 and 32 weeks of gestation were reviewed. Seven cases were further evaluated with fetal MRI. Associated findings included torcular and superior sagittal sinus dilatation in all cases and ventriculomegaly in two (25%) cases. Serial sonographic follow‐up scans demonstrated a favorable antenatal course with complete resolution before delivery in four (50%) cases. Postnatal follow‐up from 6 months to 5 years revealed normal outcome in four (50%) infants, speech disabilities in three (38%), and mild neurodevelopmental delay in the remaining case (13%). Conclusions Prenatal sonography is an effective method for diagnosing and monitoring thrombosis of the torcular herophili. As a complementary technique, fetal MRI can provide additional information to rule out cerebral parenchymal lesions secondary to hypoperfusion and associated brain malformations. According to our experience, the thrombus almost invariably resolves over time, although mild neurologic disabilities are frequent on long‐term follow‐up. © 2014 John Wiley & Sons, Ltd.